Detection of Aerolysin Gene in Aeromonas hydrophila from Suspected Farming Fishes (Cyprinus carpio), Erbil Province / Iraq - ibrahim ramadhan ibrahim; Shamall Mohamad Amin Abdullah; Abdulkarim Yasin Karim; Abdulkarim Yasin Karim2 (Zanco Journal of Pure and Applied Sciences, 2020)
Aeromonas hydrophila consider as the most common pathogenic bacteria which infect many farming fishes and due to many economical losses annually this bacteria found in fresh, brackish waters and ponds. The present study conducted to determine the most reliable method for the diagnosis of A. hydrophila from common carp (Cyprinus carpio), in Agriculture college fish farmduring a farming (May 2017 to October 2018).Results of the present study showed that 60 bacterial samples out of 115 bacterial samples were gram-negative, however 40 samples were motile and only 29 samples showed positive hemolysis on blood agar. Result of molecular diagnosis showed that only 18 bacterial samples have Aerolysin gene (1482 bp).